Flyaway - Christopher, Lucy (New York : Scholastic, 2013)
Juvenile fiction.
Keywords: Families -- Juvenile fiction; Swans -- Juvenile fiction; Wild rescue -- Juvenile fiction; Wildlife rescue -- Juvenile fiction